2017
DOI: 10.1111/jcmm.13255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of white light‐emitting diode (LED) exposure on retinal pigment epithelium in vivo

Abstract: Ageing and alteration of the functions of the retinal pigment epithelium (RPE) are at the origin of lost of vision seen in age‐related macular degeneration (AMD). The RPE is known to be vulnerable to high‐energy blue light. The white light‐emitting diodes (LED) commercially available have relatively high content of blue light, a feature that suggest that they could be deleterious for this retinal cell layer. The aim of our study was to investigate the effects of “white LED” exposure on RPE. For this, commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 67 publications
0
65
1
2
Order By: Relevance
“…In vitro and in vivo (Jaadane et al, 2015;2017) studies demonstrated that commercial LED light induce retinal injuries in which oxidative damages are involved. Enhancing the antioxidant status in the RPE cells might represents a strategy in limiting the damages produced by LED light sources (Jaadane et al, 2015, Jaadane et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo (Jaadane et al, 2015;2017) studies demonstrated that commercial LED light induce retinal injuries in which oxidative damages are involved. Enhancing the antioxidant status in the RPE cells might represents a strategy in limiting the damages produced by LED light sources (Jaadane et al, 2015, Jaadane et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It is mainly due to the fact that light with longer wavelength causes less absorption and scattering of light into the tissue than the light with shorter wavelength (e.g., blue or green). There are many reports regarding the biphasic dose–response in PBM therapy showing that the PBM effect can be positive or negative to cell viability, depending on the energy density or irradiation time 40–43. In this study, the half duty cycle was applied to 5 or 500 Hz, thereby lowering the energy densities at 5 or 500 Hz by approximately 50% compared to the energy density of CW.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible to study the mechanisms of class 2 photochemical injury through experiments on rodent model, and many studies have been based on it. Despite the fact that normative requirements seem to have correctly protected general population from acute exposure to LEDs, in recent years, some concerns have been raised within public and in scientific community, because deleterious effects of light from white LEDs were demonstrated on rat retina, at low, domestic light levels (Shang et al, 2013(Shang et al, , 2017Jaadane et al, 2015Jaadane et al, , 2017Krigel et al, 2016). Subsequently, following some of these studies, authors asked, on the base of their results, for a reduction of the current limit of radiant exposure.…”
Section: Questionsmentioning
confidence: 99%
“…This value is in good agreement with pupil size values of atropinized rat eyes measured by Van Norren and Schellekens (1990) and Van Norren and Gorgels (2011) (d = 5 mm). This last value has been used in calculations to model the retinal irradiance of eyes by Jaadane et al (2015Jaadane et al ( , 2017. Also, for possible values of rat pupil size, for nonanaesthetized animals, a range from 0.4 mm (under bright light) to 5 mm (atropinized eye) shall be considered.…”
Section: Rat Eye Pupil Sizementioning
confidence: 99%